ANALISIS TEKNO-EKONOMI RANCANGAN JARINGAN FTTH GPON DI DAERAH KABUPATEN JEMBRANA DAN TABANAN - Nugraha Putra, Bayu; Gunantara, Nyoman; Diafari Djuni, IGAK (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
In the context of fiber optic network implementation, the function of techno-economic analysis is to evaluate the costs and benefits of implementing fiber optic networks, as well as to determine the feasibility and success of the approaches to be compared in building and operating the network. Net present value (NPV), and internal rate of return (IRR) are some of the methods commonly used by investors to quantitatively evaluate the potential for technology implementation and make informed decisions about whether the investment is worth making. Consider the number of interested parties and the availability of existing backbone network. In Jembrana Regency, the Gilimanuk cluster plan produces an NPV and IRR of IDR 431,608,386 and 24.27% respectively. Meanwhile, for Tabanan Regency, Plan Cluser Marga produces NPV and IRR of IDR 853,682,479 and 35.83% respectively.